Application Method Certainty Factor in Electrical Damage - Zulkifli, Akhmad; Riandini, Meisarah; Hayadi, B. Herawan; Prasiwiningrum, Elyandri (Journal of ICT Applications System, 2023)
Electricity is need main For life people human . Electricity is used man For various type activity human . Electricity plays a big role for life , like For lighting , cooking , and so on . Almost all activity daily use electricity . Almost every home in Indonesia, both in the city nor village Already trellis with electricity . For stream and distribute electricity to each home , office nor distant institutions _ away , then needed Transformer Distribution . Transformer Distribution This own objective use special that is, to lower voltage tall to voltage low , so that the voltage used in accordance with equipment ratings electricity customer or load in general . For help in handle problem damage Transformer distribution , then one is needed branch from Knowledge computer that is System Expert . System Expert is system based computer that uses knowledge , facts , and techniques reasoning in solve problem , which usually is only can completed by one expert in field certain . (Putri, 2020). The method used in research _ This is Certainty Factor. Study This apply certainty factor method For role in diagnose damage to electricity . Based on results discussion on with choose one _ damage namely P1 ( Oil transformer go out from the transformer body ) on the study case obtained decision level accuracy that is as big That's 5.650198%. means system expert certainty factor method can overcome damage and deliver results diagnosis good at damage electricity